MAGNETIC FIELD VARIABILITY OF STARS - Bychkov, V. D.; Bychkova, L. V.; Madej, J. (Одеські астрономічні публікації, 2017)
We present in this paper a description for various types of the apparent variations of stellar magnetic fields, which we actually recognise.